(untitled) (Literary Voice, 2024)
Mankind is the only species to be gifted with the power of reasoning. Our quest to comprehend life has always been on the move. There was a time when we were completely governed by the laws of nature. However, through breakthroughs in science and technology, man has been able to evolve and exercise control. We now live in an era where our lives are governed by digital technology. Literature, cinema, and other art forms are the bases on which this is built. As movie lovers there have been times where we wished the movies had alternate endings. This stems from our own thoughts of living vicariously through the main characters. This is being facilitated by Interactive Digital Narrative in video games and movies. To understand and analyse this, the present paper takes Black Mirror: Bandersnatch to study the same. Black Mirror: Bandersnatch is an interactive movie that gives us several choices as we become the protagonist and attempt to change the fate of the protagonist in the story. Does digital technology help or harm our core values? Can art forms withstand the test of time, even in this digital era? This paper comprehends to find answers to the above questions.